Dynamic Modeling, Control, and Analysis of a Solar Water Pumping System for Libya. (24th April 2017) - Shebani, Muamer M.; Iqbal, Tariq
Abstract : In recent years, one of the suitable solar photovoltaic (PV) applications is a water pumping system. The simplest solar PV pumping system consists of PV array, DC-DC converter, DC motor, and water pump. In this paper, water pumping system sizing for Libya is evaluated based on a daily demand using HOMER software, and dynamic modeling of a solar PV water pumping system using a Permanent Magnet DC (PMDC) motor is presented in Matlab/Simulink environment. The system performance with maximum power point tracking (MPPT) based on Fractional Open Circuit Voltage (FOCV) is evaluated with and without a battery storage system. In some applications, a rated voltage is needed to connect a PMDC motor to a PV array through a DC-DC converter and in other applications the input voltage can vary. The evaluation of the system is based on the performance during a change in solar irradiation. Using Matlab/Simulink, simulation results are assessed to see the efficiency of the system when it is operating at a specific speed or at the MPPT. The results show that an improvement in the system efficiency can be achieved when the PMDC motor is running at a specific speed rather than at the peak PV power point.